The Effect of Frugality, Environment, and Social Support on Purchase Intention of Thrifting Clothing Moderated by Price Sensitivity - Abdurrahman Abdurrahman; Nuzul Hidayat (Journal of Accounting, Management, and Economic Development, 2025)
This study aims to analyze the influence of frugality, environment, and social support on the purchase intention of thrifting clothing in generation Z with price sensitivity moderation within the scope of Theory Planned of Behavior (TPB) as the main reference in this study. This research is a type of quantitative research with the main research instrument in the form of a questionnaire which was distributed online to 120 respondents who are generation Z in West Nusa Tenggara. The data was analyzed using Structural Equation Modeling – with Partial Last Square (PLS). The findings of this study show that purchase intention in thrifting clothing can be significantly influenced by frugality and environmental factors. Meanwhile, social support has a non-significant effect on purchase intention. In addition, price sensitivity is proven to strengthen the influence of frugality on purchase intention, while price sensitivity can weaken the influence of environment and social support on the purchase intention of thrifting clothing among Generation Z. This finding provides important insights for further research and can be a reference in policy-making related to environmentally friendly shopping trends, especially thrifting clothing.